Dynamic Detection of Secure Routes in Ad hoc Networks - Movahedian Attar, Niloofar (Ital Publication, 2017)
The present paper focused on ad hoc networks with an emphasis on their dynamic nature. After an introduction to ad hoc networks, there are the AODV (Ad hoc On-demand Distance Vector) routing protocol with the node malicious behaviour and consequent damages to ad hoc networks. Then, trust is described as one of the solutions for identifying secure routes when there are malicious nodes in the network. Accordingly, the paper focuses on the proposed solutions that are based on the parameter trust and the prevention of the impact of malicious networks and vulnerable connections to identify a secure route. Then, an equation is presented to calculate trust using packet forwarding rate to select a secure route for sending data packets. The proposed model was implemented on OMNET++ to evaluate the network performance. The feature of the proposed method is better performance than of the methods TVAODV and AODV. Using the proposed method, packet delivery rate increases more significantly when malicious nodes increases than that of the basic method AODV and TVAODV. There is thus a lower packet dropping rate.